Liver cirrhosis as a predisposing factor for esophageal candidiasis. Issue 3 (3rd July 2014) - Ou, Tzu‐Ming; Huang, Hsin‐Hung; Hsieh, Tsai‐Yuan; Chang, Wei‐Kuo; Chu, Heng‐Cheng; Hsu, Chin‐Hui; Shih, Yu‐Lueng; Huang, Tien‐Yu; Chen, Peng‐Jen; Lin, Hsuan‐Hwai
Summary: Background: Esophageal candidiasis (EC) often occurs in human immunodeficiency virus (HIV)‐infected patients, but is uncommon in non‐HIV‐infected patients. It is known that malignancy, diabetes mellitus, previous gastric surgery, and medications (antibiotics, proton pump inhibitors, and steroids) are risk factors for esophageal candidiasis in non‐HIV‐infected patients. However, the relationship between liver cirrhosis and esophageal candidiasis was unclear. This study aimed to elucidate the role of liver cirrhosis in esophageal candidiasis. Methods: A retrospective chart review study was conducted on non‐HIV‐infected patients with esophageal candidiasis who presented to Tri‐Service General Hospital from January 2009 to December 2012. The diagnosis of EC was primarily based on endoscopic findings. The incidence of EC in cirrhotic and noncirrhotic patients was compared. Furthermore, differences in baseline characteristics, clinical variables, and mortality after antifungal treatment between the two groups were analyzed. Results: In this study, 43, 217 non‐HIV‐infected patients were enrolled, 3017 of whom had liver cirrhosis. The incidence of EC in cirrhotic patients was higher than that in noncirrhotic patients (0.8% vs. 0.36%; relative risk = 2.2; p  < 0.001). Multivariate logistic regression analysis identified liver cirrhosis as an independent risk factor for EC (odds ratio, 1.74; 95% confidence interval, 1.06–2.87; p  = 0.029). Moreover, cirrhotic patients tended to be asymptomatic compared with noncirrhotic patients (45.8% vs. 9%; p  < 0.01). The most common coexisting endoscopic finding was reflux esophagitis (83.9%). However, antifungal treatment did not decrease the mortality of patients with EC during hospitalization. Conclusion: Liver cirrhosis is an independent risk factor for EC. EC may be asymptomatic in cirrhotic patients. Although antifungal treatment did not improve the outcome in this study, a prospective study is still required to investigate this issue.